Groove pancreatitis presenting as recurrent acute pancreatitis - Vishal Khurana; Debottam Bandyopadhyay; Sukanta Ray; Keya Basu; Avik Bhattacharyya (Archives of Medicine and Health Sciences, 2014)
A middle aged male presented with recurrent acute pancreatitis without any feature of extrahepatic biliary obstruction. Evaluation revealed mass in groove area with duodenal lumen compromise without any features of chronic pancreatitis. He underwent classical Whipple′s operation with the suspicion of periampullary tumor but histopathology was suggestive of groove pancreatitis ruling out malignancy. This case is first case to report recurrent acute pancreatitis as presentation of groove pancreatitis.